1988
DOI: 10.1007/bf00039866
|View full text |Cite
|
Sign up to set email alerts
|

Responses of wheat and barley genotypes to toxic concentrations of soil boron

Abstract: The growth and yield of seven wheat and two barley cultivars or lines, previously found to show different degrees of boron tolerance under field conditions, were compared in a pot experiment at a range of soil boron treatments . Soil treatments ranged up to 150 mg/kg applied B . Extractable B in soils ranged up to 103 mg/kg . At the highest B treatment seedling emergence was delayed, but the percentage emergence was not reduced . The degree of boron toxicity symptom expression varied between the wheat cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
87
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 14 publications
5
87
1
Order By: Relevance
“…Genotypic variation in susceptibility to B toxicity has been reported (Torun et al, 2006). Paull et al, (1988) reported wide range of intra-specific variation in response to B occurs in a number of crops, including bread wheat (Triticum aestivum L). In addition, seed germination and seedling growth are the most important phases in the life cycle of plant, and are highly responsive to the existing environment.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic variation in susceptibility to B toxicity has been reported (Torun et al, 2006). Paull et al, (1988) reported wide range of intra-specific variation in response to B occurs in a number of crops, including bread wheat (Triticum aestivum L). In addition, seed germination and seedling growth are the most important phases in the life cycle of plant, and are highly responsive to the existing environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, since B concentrations in roots are relatively low compared with those in leaves, even at very high levels of B supply, visible symptoms of B toxicity do not develop in roots (Nable et al, 1997). Thus, differential tissue tolerance may play an important role in plant tolerance of such nutritional disorder (Paull et al, 1988). On the other hand, it is likely that B-toxicity effects appear to be loosely correlated with accumulation of high concentrations of B in the shoots, which is a function both of the concentration of B in soil and the time of exposure (Reid, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Boron toxicity can affect nearly all crops that have different range of tolerance. Excessive amount of B exert negative effect on number of plant species like reduced photosynthetic efficiency in sunflower leaves [El-Shintinawy 1999], reduced chlorophyll content in cotton older leaves [Ahmed et al 2008], decreased fresh and dry matter and increased B concentration of sunflower shoots [Day 2016a[Day , 2016b, decreased height and shoot growth [Paull et al 1990] and delay in development of wheat [Paull et al 1988], decreased yield of radish [Tariq and Mott 2006], tomato [Eraslan et al 2007], rice [Koohkan et al 2008] and barley [El-Feky et al 2012]. Boron toxicity also has an impact on uptake of other micro or macro elements such as K, Ca, Mg and Na concentration [Tariq and Mott 2006] in plants.…”
Section: Introductionmentioning
confidence: 99%